Complex determinants of macrophage tropism in env of simian immunodeficiency virus. - Mori, K (1992)
Macrophage-tropic virus variants evolved during the course of infection of individual rhesus monkeys with cloned, non-macrophagetropic simian immunodeficiency virus. Specific changes in the envelope gene (env) were found to be primarily responsible for the dramatic increase in the ability of the virus to replicate in macrophages. Cloned viruses differing at nine amino acid positions in env exhibited a more than 100-fold difference in replicative capacity for primary cultures of rhesus monkey alveolar macrophages. At least five of the nine amino acid changes contributed to macrophage tropism. These determinants were distributed across the full length of env, including both the gp120 and gp41 products of the env gene. Furthermore, the emergence of macrophagetropic variants in vivo was associated with specific pathologic manifestations in which the macrophage is the major infected cell type. Thus, major determinants of macrophage tropism reside in env, they can be complex in nature, and the presence of macrophage-tropic virus variants in vivo can influence the disease course and disease manifestations.